Contracts and the products of Islamic banking - Abdul Rahman, Zaharuddin (CERT Publications Sdn. Bhd., 2010)
This book describes the original Shari'ah contracts and followed by its contemporary applications in Islamic banking products. It also provides extract quotations from the traditional books of Islamic jurisprudence, the modern Islamic finance and banking books as well as resolutions from various fiqh council especially from the Shari'ah standard developed by AAOIFI. In addition various types of generic diagrams of the products including selected issues on each product are highlighted in details. There are also attempts to address some common questions regarding Islamic banking practices. It is hope that this book will prove to be useful source material for understanding the principles, modus operandi and issues of Islamic finance.